2014
DOI: 10.1111/jth.12494
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and prevalence of circulating ADAMTS13‐specific immune complexes in autoimmune thrombotic thrombocytopenic purpura

Abstract: prevalence of circulating ADAMTS13-specific immune complexes in autoimmune thrombotic thrombocytopenic purpura. J Thromb Haemost 2014; 12: 329-36.Summary. Background: The formation of ADAMTS13-specific circulating immune complexes (CICs) may be a pathophysiologic mechanism in autoimmune thrombotic thrombocytopenic purpura (TTP), but has not been systematically investigated. Objectives: (a) To develop an assay for ADAMTS13-specific CICs; (b) to evaluate their prevalence in autoimmune TTP; and (c) to assess thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 24 publications
(37 reference statements)
0
31
0
Order By: Relevance
“…The anti-ADAMTS13 antibodies are mainly directed against the spacer domain of the protease (95% of autoantibodies) ( Figure 1). 22 However, in some acquired TTP cases with ADAMTS13 deficiency, antibodies may be undetectable which could be related to the lack of sensitivity of available methods, 23 to anti-ADAMTS13 antibodies of IgM or IgA type, 24 to an altered synthesis or secretion of ADAMTS13, 25 to consumption or further enzymatic degradation of the protease. [26][27][28] The differential diagnosis between TTP and other cytopenias in children can be challenging and 31% of initial misdiagnosis (HUS, atypical HUS, autoimmune cytopenia, hematological malignancy) have been reported.…”
Section: Acquired Ttpmentioning
confidence: 99%
“…The anti-ADAMTS13 antibodies are mainly directed against the spacer domain of the protease (95% of autoantibodies) ( Figure 1). 22 However, in some acquired TTP cases with ADAMTS13 deficiency, antibodies may be undetectable which could be related to the lack of sensitivity of available methods, 23 to anti-ADAMTS13 antibodies of IgM or IgA type, 24 to an altered synthesis or secretion of ADAMTS13, 25 to consumption or further enzymatic degradation of the protease. [26][27][28] The differential diagnosis between TTP and other cytopenias in children can be challenging and 31% of initial misdiagnosis (HUS, atypical HUS, autoimmune cytopenia, hematological malignancy) have been reported.…”
Section: Acquired Ttpmentioning
confidence: 99%
“…The same study found an association between increasing levels of ADAMTS13-specifi c CICs and the number of plasma exchanges needed to achieve remission [ 57 ]. An ELISA method has recently been developed and validated by an Italian group to detect ADAMTS13-specifi c CICs, with mean intra-and inter-assay CVs of 5.3 and 9.6 %, respectively [ 57 ]. This type of ELISA is not yet commercially available, and the potential usefulness of measuring ADAMTS13-associated CICs in clinical practice warrants further studies.…”
Section: Identifi Cation Of Adamts13 Autoantibodiesmentioning
confidence: 82%
“…A recent study demonstrated CICs in one-to two-thirds of patients with TTP, and the levels of ADAMTS13-specifi c CICs were independent from other ADAMTS13 measurements. The same study found an association between increasing levels of ADAMTS13-specifi c CICs and the number of plasma exchanges needed to achieve remission [ 57 ]. An ELISA method has recently been developed and validated by an Italian group to detect ADAMTS13-specifi c CICs, with mean intra-and inter-assay CVs of 5.3 and 9.6 %, respectively [ 57 ].…”
Section: Identifi Cation Of Adamts13 Autoantibodiesmentioning
confidence: 93%
“…The observed long‐term morbidities in this patient group (arterial hypertension, major depression, neurocognitive deficits, and, particularly, the unexplained reduced life‐expectancy) hint at a much higher chronicity of iTTP than had been anticipated. The presence of circulating ADAMTS‐13 immune complexes even years after an acute iTTP episode also suggests a chronic ongoing disease, and challenges the concept of remission in iTTP.…”
Section: Ittpmentioning
confidence: 99%